Excavations at Paithan, Maharashtra : Transformations in Early Historic and Early Medieval India. - Kennet, Derek; Rao, J. Varaprasada; Bai, M. Kasturi (Berlin/Boston : Walter de Gruyter GmbH, 2020)
Beyond Boundaries: Religion, Region, Language and the State is a research initiative hosted by the British Museum and the British Library in London. Moving beyond geographical, chronological, disciplinary and historiographical boundaries, the books in this series explore the interactions of India and her neighbors from late antiquity to the close of the medieval.
Intro -- Preface -- Table of Contents -- List of Tables -- List of Figures -- Part I Background to the project -- Chapter 1 The Scope of the Project and Its Background -- Chapter 2 Historical Context -- Chapter 3 Previous Archaeological Work at Paithan -- Part II The Excavations -- Introductory Remarks on the Excavations -- Chapter 4 The Brick Temples in Trench A -- Chapter 5 The Excavation of Trenches B, C, D, E and F -- Chapter 6 Periodisation and Dating of the Sequence -- Summary Remarks on the Excavations -- Part III The Finds -- Brief Remarks on the Finds -- Chapter 7 The Pottery -- Chapter 8 The Small Finds and Glass -- Chapter 9 The Coins -- Chapter 10 Summary of the Finds from the 1996 and 1997 Excavations -- Chapter 11 Objects Displayed in the Balasaheb Patil Government Museum -- Part IV Environmental Evidence -- Introductory Remarks on the Environmental Evidence -- Chapter 12 Archaeobotany -- Chapter 13 The Faunal Remains -- Part V Conclusions -- Chapter 14 Paithan in Its Regional, Historical and Cultural Context -- Chapter 15 Paithan Excavation: Historical, Archaeological, Geographical and Epigraphical Contexts -- Reference list -- Appendix I List of recorded contexts -- General Author Index -- General Subject Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books